Worlds of english - Woolfe, Harvey; Galloway, Mark; Saunders, Michaela (Open University Worldwide, 2011)
English has emerged as the language of global choice for business and the media, prompting millions to educate themselves and their children in its use. For new generations internationally it may be the main, or even only, language they speak. How did English become so popular, and what are the cultural ramifications of its spread? This three-part series looks at the history, use, and diversity of English around the world, exploring both its necessity for modern communication and its threat to local languages and identities.